Comparison of Autologous Conditioned Plasma Injection, Extracorporeal Shockwave Therapy, and Conventional Treatment for Plantar Fasciitis: A Randomized Trial. Issue 12 (22nd August 2013) - Chew, Kelvin Tai Loon; Leong, Darren; Lin, Cindy Y.; Lim, Kay Kiat; Tan, Benedict
Abstract : Objectives: To evaluate the efficacy of autologous conditioned plasma (ACP) compared with extracorporeal shockwave (ESWT) and conventional treatments for plantar fasciitis. Design: Randomized trial. Setting: Sports medicine center in a tertiary care hospital. Patients: Fifty‐four subjects (age range, 29‐71 years) with unilateral chronic plantar fasciitis with more than 4 months of symptoms. Methods: Subjects randomized to 3 groups: 19 to ACP and conventional treatment (ACP group), 19 to ESWT and conventional treatment (ESWT group), and 16 to conventional treatment alone. Conventional treatment included stretching exercises and orthotics if indicated. Main Outcome Measurements: Outcomes were pain‐Visual Analog Scale (VAS), American Orthopaedic Foot and Ankle Society (AOFAS) ankle‐hindfoot scale, and ultrasound plantar fascia thickness assessed at baseline before treatment and at 1 month, 3 months, and 6 months after treatment. Results: VAS, AOFAS ankle‐hindfoot scale, and plantar fascia thickness improved in all groups. Significant VAS pain score improvements in the ACP group compared with conventional treatment at month 1 ( P = .037) and for the ESWT group compared with conventional treatment at months 1, 3, and 6 ( P = .017, P = .022, and P = .042). The AOFAS ankle‐hindfoot scale score improved in the ACP group at months 3 and 6 ( P = .004 and P = .013) and, for the ESWT group, at months 1 and 3 ( P = .011 and P = .003) compared with conventional treatment. Significant improvements in plantar fascia thickness were seen in the ACP group at months 1 and 3 compared with conventional treatments ( P = .015 and P = .014) and at months 3 and 6 compared with the ESWT group ( P = .019 and P = .027). No adverse events reported. Conclusions: Treatment of plantar fasciitis with ACP or ESWT plus conventional treatments resulted in improved pain and functional outcomes compared with conventional treatment alone. There was no significant difference between ACP and ESWT in terms of VAS and AOFAS ankle‐hindfoot scale improvements, although the ACP group demonstrated greater reductions in plantar fascia thickness.